PERLINDUNGAN HUKUM ATAS KEKERASAN SEKSUAL BAGI KAUM PENYANDANG DISABILITAS TUNA NETRA - Rama Yanuar Rizky; Ahmad Mahyani (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
So far, people with disabilities have experienced various kinds of discrimination, especially women. Women with disabilities are very vulnerable to being victims of violence, including sexual violence. Various reports in the media show that there are many women with disabilities. Over time, we are often surprised by the emergence of several cases involving persons with disabilities. One of the cases experienced by persons with disabilities is being a victim of rape. The situation of disabled people who are victims of sexual violence is worrying, not only because they are a vulnerable group, but also because many do not receive legal protection. From 2015 to 2016, there were 74 cases of sexual violence in Yogyakarta, of which 3 were handled through legal channels and other cases were medical, psychological and even medical, psychological and even the same way, the Advocacy Center for Women and Children with Disabilities (Advocacy Center for Women and Children with Disabilities). Persons with Disabilities). SAPDA) DIY published a study in 2016 which found that 84.5% of violence against women with disabilities did not have legal protection. Since the enactment of Law No. 8 of 2016 concerning Disabilities which was ratified by President Joko Widodo on April 15, 2016, there is no longer any mention of the term "disability" for people with physical limitations. The Disability Policy is the commitment of the Indonesian government to regulate the protection and fulfillment of the rights of people with disabilities in Indonesia